A PRACTICAL APPLICATION OF KNOWLEDGE MANAGEMENT TO THE FRONT OFFICE OF A CONTACT CENTER - Tavares, Samuel Ribeiro (2012)
This paper aimed at developing and testing a proposal based on knowledge management to enablea contact center operation to harvest the benefits of workforce empowerment while minimizing the risks ofsuch a managerial approach. In an experimental, interventionist research, flavored with a critical orientation,the case of such an operation in São Paulo was studied. In light of the findings, it is possible to conclude,without any room for generalization, however, that knowledge management can contribute to an effectiveimplementation of the empowerment approach in contact centers.